The Effect Of Cash Flow On Stock Prices In Manufacturing Companies For The Consumer Goods Sector Consumer Goods Sector - Ayu Kurnia Sari; Hendra Saputra; Jonathan Pakpahan; Sumariaty Br Manurung (International Journal of Management, Economic and Accounting, 2024)
This study aims to determine the effect of operating cash flow on stock prices through earnings persistence as an intervening variable in manufacturing companies in the food and beverage consumer goods sector. The data needed in this study were collected using documentary techniques. The type of data used in this study is secondary data. The method used to process data is descriptive statistical method and multiple linear regression method with Ordinary Least Squares (OLS) approach. The tool used in the research is SPSS version 23. The results of the Partial test or t test show that the operating cash flow variable does not have a significant and partial effect on the dependent variable, namely the market price. The t-test results show a significant value of 0.767 greater than significant (a) of 5%. Thus globally these variables cannot be used in analyzing market prices. Based on the model summary table, the value of R2 or R Squere is 0.027, this indicates that the contribution of operating cash flow and earnings persistence is 2.7% while the remaining 97.3% is the contribution of other variables.